Organic Repurchase Intention: Role of Attitude and Consumer Satisfaction - Kaleb El Nusa Pardede; Heriyadi Heriyadi; Ilzar Daud; Juniwati Juniwati; Wenny Pebrianti (Penerbit Goodwood, 2026)
Purpose: This research seeks to explore how attitude and satisfaction serve as mediating variables in the relationship between environmental concern and health consciousness with consumers' intention to purchase. Research Methodology: This study employed a quantitative methodology and was carried out in Indonesia. It involved 206 participants who had experience in purchasing and using organic skincare products from local brands, including Sensatia Botanical, Skin Dewi, Avoskin, N’Pure, and Runa Beauty. Data was collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. Results: The findings indicate that both environmental concern and health consciousness positively and significantly influence attitude and satisfaction. Both psychological factors attitude and satisfaction were found to play a mediating role in the connection between environmental and health awareness and consumers' intentions to repurchase organic skincare products. Conclusions: Environmental concern and health consciousness significantly influence attitudes and satisfaction, which in turn drive repurchase intention for organic skincare products. These findings highlight the importance of value-based marketing focused on health and environmental sustainability to build consumer loyalty. Limitations: The study is limited to respondents aged 17–44 years and predominantly from the Kalimantan region. It did not take into account other variables such as green trust or perceived behavioral control. Contribution: This study contributes to the organic skincare industry, marketers, and academics in understanding the importance of building consumer attitude and satisfaction based on environmental and health values.